Arrangements for Consensus-Based Deliberation in the Settlement of Industrial Relations Disputes that are Harmonious and Just - Arifin, Ariani Arifin; Riza, Marwati; Bachri, Syamsul; Supardi, Muhammad (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2026)
The principle of deliberation and consensus is the spirit of the Pancasila industrial relations system in Indonesia, which aims to create a balance between workers' rights and the sustainability of employers' businesses. This study aims to analyze the legal transformation of the deliberation and consensus mechanism in resolving industrial relations disputes, starting from the era of Law Number 22 of 1957 to Law Number 2 of 2004 (the PPHI Law). The research method used is normative or doctrinal legal research with a statutory approach and library research. The results show that in the era of Law No. 22 of 1957, the dispute resolution mechanism was authoritative, where the state through P4D/P4P dominated the final decision and placed deliberation only as an administrative formality. In contrast, after the enactment of the PPHI Law, there was a paradigm shift towards an autonomous-participatory system that requires bipartite negotiations as an absolute requirement before litigation. However, this implementation still faces challenges in the form of unequal bargaining power and issues of good faith that often trigger "forced consensus." This study concludes the need for a reconstruction of norms that allow law enforcement to test substantive good faith in the bipartite process to realize harmonious social justice for the world of work in Indonesia.